Exercise stress echocardiogram for the evaluation of change in the ventricular–arterial interaction after thoracic endovascular aortic repair. (22nd October 2018) - Hiraoka, Arudo; Toki, Misako; Hayashida, Akihiro; Chikazawa, Genta; Yoshida, Kiyoshi; Sakaguchi, Taichi; Yoshitaka, Hidenori
Abstract: OBJECTIVES: The aim of this study was to explore, with exercise echocardiography, the potential impact of thoracic endovascular aortic repair (TEVAR) on the ventricle–aorta coupling, based on the hypothesis that the interaction between the ventricle and aorta may be influenced by an increase in aortic stiffness due to the stent graft. METHODS: Of the patients who underwent isolated TEVAR for thoracic aortic diseases between April 2016 and December 2016, changes found in haemodynamic and echocardiographic parameters between the control ( n = 17) and TEVAR ( n = 30) groups were analysed by a stress echocardiogram. RESULTS: The end-systolic elastance significantly increased with stress in both groups [from 3.0 (2.5–4.5) mmHg/ml to 4.8 (3.7–6.5) mmHg/ml, P < 0.001, in the control group and from 2.9 (2.0–3.5) mmHg/ml to 3.4 (2.6–4.2) mmHg/ml, P < 0.001, in the TEVAR group]. The arterial elastance significantly elevated only in the TEVAR group [from 1.6 (1.3–1.8) mmHg/ml to 1.7 (1.5–2.0) mmHg/ml, P = 0.007] and arterial elastance/end-systolic elastance (ventricular–arterial coupling) significantly decreased only in the control group [from 0.5 (0.4–0.7) to 0.4 (0.3–0.5), P = 0.002, in the control group and from 0.6 (0.4–0.8) to 0.5 (0.4–0.6), P = 0.10, in the TEVAR group]. In the control group, the change in end-systolic elastance and ventricular–arterial coupling tended to be greater ( P = 0.002 and 0.07). CONCLUSIONS: An exercise echocardiogram showed the underlying influences of TEVAR on the interaction between the heart and aorta. TEVAR may have the potential to suppress left ventricular contractile capacity and increase cardiac afterload during exercise. Clinical trial registration number: A201770-01.